An internet-based educational intervention for mothers targeting preschoolers' weight management promotion (PWMP): a pilot study - Fazlollah Ghofranipour; Najmeh Hamzavi Zarghani; Eesa Mohammadi; Ali Asghar Haeri Mehrizi; Mahmoud Tavousi; Marieke De Craemer; Greet Cardon (BMC, 2022)
Abstract Background The prevalence of overweight and obesity among children has raised public health concerns. This study aimed to design and evaluate a behaviour change intervention program to promote weight management among Tehranian preschoolers. Methods The PRECEDE-PROCEED model is one of the most popular models in health education used to develop and evaluate most educational interventions. In this one-group pre and post-pilot study, 13 mothers of preschoolers were recruited from preschools in Tehran (the capital of Iran), in August 2020. Mothers received a six-week educational intervention, including text messages and educational videos via WhatsApp, to increase their self-efficacy to overcome barriers changing their children's lifestyle. Mothers reported preschoolers' height and weight to assess Body Mass Index and filled out the Food Frequency Questionnaire, the Persian version of the children's health-related quality of life questionnaire, and demographic features. The "Children's physical activity and sedentary behaviors checklist," newly designed by the researchers, was also filled out by mothers. These behaviors were measured according to the minutes that children were involved in these activities in a day, and the days they spent in a week for them. All variables were measured at baseline, immediately after the intervention and three months later. Data analysis was performed using SPSS IBM statistics version 22. Friedman test was used to evaluate changes over time. Results The findings demonstrated that the mean BMI z-score stayed steady between baseline, immediately after the intervention and after three months (P = 0.60). Besides, after three months, the intervention programme led to a decrease in soft drink consumption (P = 0.001), and an increase in parental perception of their child's general health (P = 0.05), the parental concern regarding their child's emotional and physical health (P = 0.002) and minutes of physical activity per day (P = 0.02). However, fruit intake decreased (P = 0.01), and simple sugar, such as cube, increased (P = 0.03). Conclusion Results from this study are promising but should be interpreted with caution and should be replicated on a larger scale and compared with a control group to evaluate whether effects are maintained in a larger sample.